Vegetative and reproductive plant height of species populations in relation to land use changes in Mediterranean rangeland ecosystems - Papadimitriou M.; Tsougrakis Y.; Papanastasis V.P. (Pastoralism and sustainable development: proceedings, 2021)
Plant height is a functional trait that is directly related with plant competitive ability and its capacity to tolerate or avoid disturbance and environmental stress. The aim of this paper was to study the vegetative and reproductive plant height of plant populations of the same species in relation to land use changes in Mediterranean rangelands. At the area of Lofiskos, Lagadas County, Thessaloniki, N. Greece, four land use types were selected: a) abandoned arable field, b) grassland, c) open shrubland and d) dense shrubland with four replicates each, representing four stages of secondary succession after land use extensification and/ or abandonment. Vegetative and reproductive plant height of the populations of plant species that were abundant in at least two of the land use types was measured. Vegetative plant height was significantly different between the populations of the same species for the 71% of the species under study, while reproductive plant height was significantly different for the 64% of the species studied. In both cases, the majority of the species appeared significantly higher height in their populations in the advanced stages of succession. Vegetative and reproductive plant height of species population’s responds to land use changes caused by extensification and/or abandonment in Mediterranean rangelands.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)